Skin Delivery of Hydrophilic Biomacromolecules Using Marine Sponge Spicules - Zhang, Saiman; Ou, Huilong; Liu, Chunyun; Zhang, Yuan; Mitragotri, Samir; Wang, Dexiang; Chen, Ming (Molecular pharmaceutics, 2017)
We report the development of sponge Haliclona sp. spicules, referred to as SHS, and its topical application in skin delivery of hydrophilic biomacromolecules, a series of fluorescein isothiocyanate-dextrans (FDs). SHS are silicious oxeas which are sharp-edged and rod-shaped (∼120 μm in length and ∼7 μm in diameter). SHS can physically disrupt skin in a dose-dependent manner and retain within the skin over at least 72 h, which allows sustained skin penetration of hydrophilic biomacromolecules. The magnitude of enhancement of FD delivery into skin induced by SHS treatment was dependent on its molecular weight. Specifically, SHS topical application enhanced FD-10 (MW: 10 kDa) penetration into porcine skin in vitro by 33.09 ± 7.16-fold compared to control group (p < 0.01). SHS dramatically increased the accumulation of FD-10 into and across the dermis by 62.32 ± 13.48-fold compared to the control group (p < 0.01). In vivo experiments performed using BALB/c mice also confirmed the effectiveness of SHS topical application; the skin absorption of FD-10 with SHS topical application was 72.14 ± 48.75-fold (p < 0.05) and 15.39 ± 9.91-fold (p < 0.05) higher than those from the PBS and Dermaroller microneedling, respectively. Further, skin irritation study and transepidermal water loss (TEWL) measurement using guinea pig skin in vivo indicated that skin disruption induced by SHS treatment is self-limited and can be recovered with time and efficiently. SHS can offer a safe, effective, and sustained skin delivery of hydrophilic biomacromolecules and presents a promising platform technology for a wide range of cosmetic and medical applications.